Estudo e avaliação da percepção do usuário de faixas de pedestres modificadas - Canavese, Patricia Consorti (Universidade Federal de São Carlos, 2022)
Currently, there are a large number of traffic accidents around the world, causing damages due to the loss of lives and materials, requiring government investment to repair the damage caused. In Brazil and underdeveloped countries as a whole, the reality is even more serious. To alleviate this situation, inspection systems, specific laws, and improvement of roads, among others, are implemented to increase the safety of road users, whether drivers, pedestrians, or cyclists. It is in this scenario that traffic signal plays an important role. Among the existing types of signage, the crosswalk is important, as most accidents involve pedestrians. Faced with such a scenario, this research shows the analysis of the impact caused by the use of the Modified Pedestrian Crossing. In this research, the Rank Order Method was used to analyze four different types of crosswalks in three criteria: visual impact, safety perception, and confusion caused. The Pedestrian Crossings that caused greater and less visual impact were, respectively, the Diamond type and the Zebra cross walk type. The ones that brought the greatest and least sense of security were, in this order, the Blue Background type and the Diamond type. Finally, the most confusing is the Diamond type and the least confusing is the Zebra cross walk type. These results show that the use of colors and elements in the crosswalks contributed to increasing the results in each of the parameters analyzed.
Study and evaluation of user perception of modified pedestrian crossings
Keywords: Sinalização; Faixas de pedestres modificadas; Acidente de trânsito; Impacto Visual; ENGENHARIAS::ENGENHARIA DE TRANSPORTES::PLANEJAMENTO DE TRANSPORTES